Perspectives on the COVID-19 Pandemic: Truth and Trust - Hughes, Tyler G. (Journal of Lumbini Medical College, 2020)
When one examines life in various countries of the world regardless of type of government, health system, or even culture, one sees the great diversity of the world but also large areas of commonality among all people and all places. The twentieth century’s history is one of almost constant war, two of those wars having affected the majority of the global population, but only one event parallels today’s pandemic in impact on almost every individual on planet Earth: the great pandemic of 1918, which by various accounts took between 20 to 100 million lives over a three-year period.